The Influence of YouTube Media Use on the Ability to Write Narratives About My Vacation in 3rd Grade Elementary School Students - Agustin, Nita; Juliana, Aat; Tesa Al khusaimah; Mascita, Dede Endang; Rosmaya, Elin (Journal of Education Technology, 2025)
The narrative writing skills of elementary school students remain a significant challenge, as evidenced by difficulties in developing ideas, limited vocabulary, and a low interest in writing activities. This condition negatively affects the quality of students’ written work, particularly in terms of structure, language use, and paragraph coherence. This study aims to analyze the effect of using YouTube media on narrative writing skills with the theme “My Holiday” among third-grade elementary school students. The research employed a quasi-experimental method with a pretest-posttest control group design. The subjects involved 27 students divided into experimental and control groups. Data were collected through narrative writing tests administered before and after the treatment, using a narrative writing test sheet as the instrument. Data analysis was conducted using paired sample t-tests and Cohen's d effect size calculation. The results indicated a significant improvement in students' narrative writing abilities after learning with YouTube media, with a significance value of p = 0.000 and a large effect size (Cohen’s d = -1.564). Conceptually, YouTube media proved effective in enhancing students' ability to develop ideas, enrich vocabulary, and improve narrative structure. These findings recommend YouTube media as an alternative, relevant, and contextual literacy tool for writing instruction in elementary schools.